Uji Adaptasi Padi Sawah (Oryza sativa L.) Galur Harapan terhadap Hasil dan Ketahanan Penyakit Tungro di Subak Lepang, Desa Takmung, Kabupaten Klungkung - PUTU SUGITA; GEDE WIJANA; I KETUT SUADA (Fakultas Pertanian Universitas Udayana, 2018)
Adaptation Test of Paddy Rice (Oryza sativa L.) Expected Line Against Results and Disease Resilience Tungro Disease in Subak Lepang, Takmung Village, Klungkung Regency. Adaptation test of expected line paddy (Oryza sativa L) on its yield and tungro-resistance in Subak Lepang were conducted from July to September 2016. The aims of this test were to examine the growth and productivity of expected line paddy and its resistance to tungro. Twelve lines and two comparated varieties were set using Randomized Block Design. Dependent variable were growth, yield and age of 50% productive spikelets were gain, duration of yield, number of panicles, length of panicle, number of filled spikelets in each panicle, number of empty spikelets in each panicle, total spikelets, sweed set, weight of 1000 spikelets, weight of 14% water content of 1000 spikelets, weight of dry spikelets in a hectare (ton) and precentage of tungro’s invation. Statistical analisis showed that BP16732E-1 as expected line was well adapted to test, which were give better growth, yield and tungro resistency, and 13.139% higher yield compared to Ciherang variety. Future research on adaptation in different season and ecosystem should be conducted to determine this strain as new supreme strain.